Assessment of therapeutic effects of Nigella sativa against chronic lead acetate-induced reproductive dysfunction in male Sprague-Dawley rats - Assi, Mohammed Abdulrazzaq; Mohd Noor, Mohd Hezmee; Abba, Yusuf; Rajion, Mohamed Ali; Haron, Abd. Wahid; Mohd Yusoff, Md Sabri (Springer, 2017)
Lead acetate (LA) is a toxic compound that has detrimental effects on the male reproductive system, such as decreased testicular size and function, low androgen hormone concentration, and altered testicular histology. While Nigella sativa (NS) has been shown to possess a handful of therapeutic benefits, few studies have shown its effect on damage caused by lead acetate toxicity in the male reproductive system. In this study, 75 Sprague-Dawley rats were divided into 3 groups of 25 rats, which were further subdivided into 5 subgroups each. Group 1 (negative control) was given distilled water, group 2 (positive control (PC)) administered 10 mg/kg of lead acetate (LA) orally/daily, while groups 3 (T1), 4 (T2), and 5 (T3) were given LA 10 mg/kg and graded concentrations (100, 150, and 200 mg/kg) each of NS. One group each, comprising of 25 rats, was euthanized at days 30, 60, and 90 for collection of blood plasma, epididymis, and organ tissues fixed in 10 % buffered formalin at each time interval. The right caudal epididymis was homogenized and used for the determination of spermiogram. Plasma was used for the determination of testosterone (TS), follicle stimulating hormone (FSH), and luteinizing hormone (LH) and estradiol (EST) using radioimmunoassay kits. There was reduced number of spermatogenic cells and epididymal sperm reserves in the PC group in comparison to the treatment groups. The level of TS was lower (p < 0.05) in the PC group at 90 days, while FSH was lower (p < 0.05) in T3 at 30 days and LH was higher (p < 0.05) in T1 at 90 days. The concentration of EST was lower (p < 0.05) in the PC, T1, and T2 at all time points, while the T3 group had the higher EST concentration that was similar to the control group. There was a decreased level of superoxide dismutase (SOD) and total glutathione (GSH) in the PC group and an increased GSH level in the T3 group. Sperm concentration, viability, and motility were adversely affected by LA, while concurrent treatment with NS significantly (p < 0.05) improved these parameters. This study showed the detrimental effects of LA on spermatogenesis, TS levels, and antioxidant defenses; however, these adverse effects were alleviated by oral NS administration.